Long-Term Impact of Hepatitis C Virus Eradication on Liver Stiffness in Egyptian Patients - Talaat Zakareya; Mostafa Elhelbawy; Hassan Elzohry; Mohamed Eltabbakh; Mohamed Deif; Mohamed Abbasy (Canadian Journal of Gastroenterology and Hepatology)
Background/Objectives. Liver fibrosis is the inevitable end result of chronic hepatitis C (HCV) infection and is responsible for almost all liver-related complications. After the big advancement in therapeutics of HCV, liver fibrosis would expectedly improve after viral clearance. Many studies showed significant improvement of liver fibrosis shortly after successful treatment with direct acting antiviral agents (DAAs); however, the long-term changes have been scarcely addressed in the literature. We aimed to trace dynamical changes in liver stiffness 1, 3, and 5 years after HCV eradication. Methods. Liver stiffness measurements (LSM) have been serially assessed 1, 3, and 5 years after HCV clearance in 655 patients who have been treated with DAAs. Results. The mean age was 51.44 ± 10 years. 73% of patients were males. 48% were cirrhotics. In noncirrhotics, the mean LSM was significantly decreased from 8.29 ± 2.3 kPa to 4.03 ± 1.0 kPa p<0.0001 at the end of the follow-up. Likewise, LSM decreased in cirrhotics from 29.66 ± 14.25 kPa to 22.50 ± 11.16 kPa p<0.0001. The proportions of F1, F2, F3, and F4 patients at the baseline were 17.7%, 17.9%, 16.6%, and 47.8%, which became 56.5%, 4.1%, 4.9%, and 34.5%, respectively, with a substantial reversal of cirrhosis in 87 patients (27.7%) at the end of follow-up. Conclusions. There was an overall significant regression of liver stiffness in all patients after sustained HCV eradication. Liver stiffness reflecting mild fibrosis (F0–F2) usually improves shortly after treatment, while measurements reflecting advanced fibrosis (F3–F4) take a longer time to regress to lower fibrosis stages.